Hospital Mental Health Admissions in Women after Unsuccessful Infertility Treatment and In Vitro Fertilization: An Australian Population-Based Cohort Study - Stewart, Louise; Holman, C. D.; Semmens, James; Preen, D.; Mai, Q.; Hart, R. (Public Library of Science, 2015)
Objective - To examine the association between in vitro fertilization (IVF) and later admission to hospital with a mental health diagnosis in women who remained childless after infertility treatment. Methods - This was a population-based cohort study using linked administrative hospital and registry data. The study population included all women commencing hospital treatment for infertility in Western Australia between the years 1982 and 2002 aged 20–44 years at treatment commencement who did not have a recorded birth by the end of follow-up (15 August 2010) and did not have a hospital mental health admission prior to the first infertility admission (n=6,567). Of these, 2,623 women had IVF and 3,944 did not. We used multivariate Cox regression modeling of mental health admissions and compared women undergoing IVF treatment with women having infertility treatment but not IVF. Results - Over an average of 17 years of follow-up, 411 women in the cohort were admitted to hospital with a mental health diagnosis; 93 who had IVF and 318 who did not. The unadjusted hazard ratio (HR) for a hospital mental health admission comparing women who had IVF with those receiving other infertility treatment was 0.50 (95% confidence interval [CI] 0.40–0.63). After adjustment for age, calendar year and socio-economic status the HR was 0.56 (95% CI 0.44–0.71). Conclusions - IVF treatment is associated with a reduced risk of hospital mental health admissions in women after unsuccessful infertility treatment. This may be explained by the healthy cohort effect.